THE POTENCY OF BOTANICAL INSECTICIDES TO CONTROL Aphis gossypii (HEMIPTERA:COCCOIDEA:APHIDIDAE) ON PATCHOULI PLANT - Mardiningsih, Tri Lestari; Tarigan, Nurbetti; Sukmana, Cucu; Kardinan, Agus (Buletin Penelitian Tanaman Rempah dan Obat, 2014)
Attack of Aphis gossypii is one of constraints in cultivating of patchouli plant. An experiment with the purpose to examine the effectiveness of botanical insecticides to A. gossypii on patchouli plant. The experiment was carried out in Research Station of Indonesian Spice and Medicinal Crops Research Institute, at Cicurug, Sukabumi from June to October 2011. The experiment was arranged in a Randomized Block Design, nine treatments and three replications. The treatments were mixing of neem oil + soap nuts, neem oil + clove oil, neem oil + citronellal oil, neem oil + clove oil + citronellal oil, citronellal oil, clove oil, neem extract, carbosulfan, and control. Patchouli plants were planted with spacing of 40 cm x 60 cm. The number of plant population plot-1 was 25 plants and the number of sample plot-1 for observation was five plants. Sampling of observed plants was conducted diagonally. Observation was carried out by counting population of A. gossypii on one shoot. Application of insecticides was conducted one day after the first observation. Interval of application was every week, conducted eight times. Other parameters observed were plant height and production of patchouli. Results showed that all treatments of botanical insecticides were effective to decrease of A. gossypii population. The most effective treatment was that of neem extract with the value ofÂ  efficacy was more than 80% occurred at seven assessments. Plant high between treatment is not significant different.